Collaborative Governance for Social Rehabilitation of The Elderly in The City of Sukabumi - Oktafiani, Ayu Chori Hidayah; Amirulloh, M. Rijal; Mulyadi, Andi (Jurnal Ilmiah Ilmu Administrasi Publik, 2024)
This study aims to analyze the implementation of Collaborative Governance in basic social rehabilitation for the elderly in Sukabumi City. The focus of this research is to understand how collaboration among various stakeholders can enhance the effectiveness of services for the elderly. The research method used is qualitative with a case study approach, involving in-depth interviews with six informants from various institutions involved in elderly services, including the Social Affairs Office, the Health Office, and the Elderly Institutions (LLI). The results show that initial conditions, such as imbalances in resources and knowledge, affect the effectiveness of collaboration. Good institutional design, with clear basic rules and planning, has proven essential in guiding and facilitating collaboration. Facilitative leadership also plays a crucial role in ensuring the smooth process of collaboration, supported by related parties who help guide and motivate stakeholders. The collaborative process, involving intensive communication, trust-building, and joint strategic planning, yields tangible benefits for elderly services. These findings affirm that trust, a shared mission understanding, and strategic planning are key factors in the success of Collaborative Governance for the social rehabilitation of the elderly in Sukabumi City.